Clinical outcome of infants younger than two months in children ward of a tertiary care hospital, Nepal - Shah, Ganesh; Dharel, Dinesh; Shah, Anish K; Sapkota, Bikal; Bhattarai, Asmita (Journal of Patan Academy of Health Sciences, 2016)
Introductions: Newborn and young infants are most vulnerable for preventable deaths, particularly in developing countries. This study was conducted to see the clinical profile and outcome of infants less than two months of age admitted in children ward of Patan Hospital. Methods: This descriptive retrospective study was conducted at Patan Hospital, over 12 months from April 2014 to March 2015. Hospital records of all admitted infants aged less than two months were reviewed. The demographic characteristics, clinical profile and clinical outcome were descriptively analyzed. Results: Out of 2062 admissions in children ward, 614 (29.8%) were infants aged less than two months, out of which 482 were neonates less than 28 days. Among these neonates, 114 were inborn. Out of 436 infections, blood culture was positive in 37 (8.9%). There were 4 (0.04%) deaths, 4 (0.04%) referral and 22 (0.25%) left against medical advice. Infection 436 (436) was the commonest cause of illness, of which neonatal sepsis was 163 (37.4%), pneumonia 130 (30%) staphylococcal skin infection 39 (8.7%) and UTI 34 (7.8%). There were 71 (11.6%) cases of neonatal hyperbilirubinemia. Blood culture was positive in 55 (9%) with CONS being the commonest organism isolated; 19 (51.3%). Conclusions: Children ward contributes significantly to the care of sick infants less than two months of age, especially out born ones, requiring neonatal care facility in tertiary level hospital of Nepal. As most admissions are for infection, followed by hyperbilirubinemia, pediatrics wards need to be equipped and staffed accordingly to meet the need of sick young infants. Journal of Patan Academy of Health Sciences. 2016 Dec;3(2):15-18